2014
DOI: 10.1007/s00586-014-3170-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of scoliosis in Rett syndrome: cord monitoring and complications

Abstract: Scoliosis surgery in patients with Rett syndrome carries a very high rate of complications and an average hospital stay approaching 3 weeks. Both caregivers and surgeons should be aware of this when planning any intervention. These patients frequently have useful lower limb function and spinal cord monitoring is a valid tool to aid in its preservation. We would suggest aggressive optimisation of these patients prior to surgery, with an emphasis on nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…These results extend our understanding of interactions between scoliosis and overall clinical severity. Surgical correction of scoliosis is mostly successful but has a very high rate of complications with a prolonged hospital stay 49 . Other orthopedic symptoms include hip displacement and a high prevalence of fractures 50 52 , which can be diminished with intravenous bisphosphonates treatment 53 .…”
Section: Skeletal Systemmentioning
confidence: 99%
“…These results extend our understanding of interactions between scoliosis and overall clinical severity. Surgical correction of scoliosis is mostly successful but has a very high rate of complications with a prolonged hospital stay 49 . Other orthopedic symptoms include hip displacement and a high prevalence of fractures 50 52 , which can be diminished with intravenous bisphosphonates treatment 53 .…”
Section: Skeletal Systemmentioning
confidence: 99%
“…First, using monopolar stimulation with a sternal electrode as an anode was found to yield similar lower-limb responses to those yielded by bipolar stimulation, and can therefore be used to monitor spinal pathways during standard surgery for scoliosis involving arthrodesis with posterior instrumentation. Such a procedure represents an alternative method to the usual SEPs that cannot give full satisfaction in all patients or to tcMEPs when there are concerns over their use in patients with epilepsy such as children with Rett syndrome [21]. Second, where indicated, monopolar stimulation allows for the combined monitoring of the spinal cord and the brachial plexus within a single stimulation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…As spinal surgery generally has greater length, complexity, and risk than other pediatric orthopaedic procedures 27 , one might assume that patients with Down syndrome may have greater risk of surgical complications after spinal surgery. Patients with various types of syndromic scoliosis have higher surgical risk, with higher rates of postoperative complications 20,[28][29][30][31][32][33][34][35][36][37] . Levy et al reported complication rates in syndromic cases including wound infection (14.3%), respiratory issues (14.3%), implant failure (35.7%), and pseudarthrosis (28.6%) 38 .…”
Section: Discussionmentioning
confidence: 99%